Spontaneous-timed versus controlled noninvasive ventilation in chronic hypercapnia – a crossover trial - Kerl, Jens (Med Devices (Auckl), 2019)
Background: There is an ongoing debate about optimal ventilator modes and settings during noninvasive ventilation (NIV). Objectives: To compare the effect of spontaneous-timed (ST) and controlled NIV on carbon dioxide reduction in patients suffering from chronic hypercapnia. Methods: Night and daytime blood gas analysis, lung function tests and 6 minute walking distance tests (6MWD) were done before and after every 6-week treatment. Results: This randomized prospective crossover trial included 42 patients. Pooled data analysis showed a decrease of nocturnal CO(2) from 54.8±5.9 mmHg to 41.6±5.5 mmHg during ST ventilation (p<0.01) and from 56.2±7.5 mmHg to 42.7±5.4 mmHg during controlled NIV (p<0.01) with no difference between treatment forms (p=0.30). Daytime CO(2) levels decreased from 49.3±5.5 mmHg to 45.6±4.5 mmHg when spontaneous timed ventilation was applied (p<0.01) and from 52.2±6.8 mmHg to 44.9±21114.4 mmHg in case of controlled ventilation (p<0.01) The amount of CO(2) reduction was 3.8±5.6 mmHg after ST mode and 7.3±6.8 mmHg controlled ventilation (p<0.05). Nocturnal ventilator use was 5.7±2.1 and 6.7±2.3 hours for ST and controlled ventilation respectively (p=0.02). There was no effect on walking distance and lung function. Conclusion: Controlled NIV showed improved compliance compared to ST ventilation. We observed similar CO(2) reductions during nocturnal ventilation, however controlled ventilation achieved a higher reduction of daytime CO(2) levels.